Potential Water Recovery from Biomass Boilers: Parametric Analysis - Daniele Dondi; Cristina D. López Robles; Anna Magrini; Marco Cartesegna (Computation, 2021)
A fundamental component of the losses of convection boilers is localized in the warm fumes that are expelled. In the warm fumes, not only energy is lost, but water is also formed from the combustion reaction in the form of steam which is expelled through the exhaust. Modern fuel boilers recover both the heat from the fumes and the latent heat of condensation from water vapor. Depending on the chemical composition of the fuel, different amounts of steam are produced together with heat and different combustion conditions, such as air in excess. In this article, a computational tool was established to simulate a combustion system mainly (but not only) focusing on the prediction of the amount of water produced. In fact, while steam in fossil fuel boilers is commonly condensed, this is not so when the fuel is a biomass. Furthermore, biomasses could contain moisture in different amounts, thus affecting the production of water and the heat of combustion. The study shows that a ten-fold amount of water is formed from biomass combustion with respect to fossil fuels (when the same energy output is produced). As a result, the recovery of water is amenable in biomasses, both from the energetic point of view and for liquid water production. In fact, the water recovered from the fumes might be also reused in other processes such as the cleaning of fumes or agriculture (after treatment).